Is There an Internal Link between Seeing a Human and Seeing One to Whom Moral Consideration Is Due? - Ariso Salgado, José María (Taylor & Francis Group, 2024)
Is There an Internal Link between Seeing a Human and Seeing One to Whom Moral Consideration Is Due?
Keywords: moral consideration; human; philosophy